Karakteristik Palm Oil Biodiesel dan Performa Mesin Diesel : A Review - Hutomo Jiwo Satrio; Yuliarto Joko Sumbogo; Wibi Pramanda (Creative Research in Engineering (CERIE), 2024)
This article is a descriptive review study on palm oil biodiesel and its comparison with diesel fuel. Crude Palm Oil (CPO) is the best raw material for biodiesel because it has similar fuel specifications to diesel fuel. Fuel specifications according to American Standard Testing and Material (ASTM) and European Standard (EN) specifications are kinematic viscosity, density, and flash point. Palm oil biodiesel has a higher Brake Specific Fuel Consumption (BSFC) value and a lower Brake Thermal Efficiency (BTE) value compared to diesel. Palm oil biodiesel has higher NOx emissions, but lower HC and CO emissions, than diesel. In addition, palm oil biodiesel can be used in diesel engines with little or no modification. It has higher density, cooler flow problems and lower calorific value. Biodiesel can be blended with diesel and used in various concentration ratios to produce biodiesel blends that have properties that comply with international standards on diesel engine fuel and emissions, resulting in improved diesel engine performance and reduced emissions. The B20 and B30 biodiesel blend compositions are the best blend compositions based on the balance between engine efficiency and emission reduction due to the optimal balance between engine performance and environmental benefits. The B20 and B30 biodiesel blends show significant reductions in CO and HC emissions, achieving reductions of about 10% to 25% compared to diesel. The decrease in BTE and increase in BSFC are still proportional, so they do not compromise overall fuel efficiency too much.